2016
DOI: 10.1177/0271678x16645112
|View full text |Cite
|
Sign up to set email alerts
|

Still cooling after all these years: Meta-analysis of pre-clinical trials of therapeutic hypothermia for acute ischemic stroke

Abstract: Therapeutic hypothermia is the most potent neuroprotectant for experimental cerebral ischemia, illustrated in a 2007 meta-analysis published in this journal. To address recent therapeutic nihilism, we systematically reviewed recent experimental literature. Quality scoring showed considerable improvement in study design. Using several outcome measures in a variety of models and species, therapeutic hypothermia was protective compared with normothermia, with powerful and statistically significant normalized trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 16 publications
1
57
0
1
Order By: Relevance
“…Therefore, transarterial regional hypothermia is strongly expected to become a novel attractive treatment for acute ischemic stroke because of its rapid cooling action and fewer systemic side effects (Dumitrascu et al, 2016;Esposito et al, 2014;Kurisu et al, 2015). Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, transarterial regional hypothermia is strongly expected to become a novel attractive treatment for acute ischemic stroke because of its rapid cooling action and fewer systemic side effects (Dumitrascu et al, 2016;Esposito et al, 2014;Kurisu et al, 2015). Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015).…”
Section: Introductionsupporting
confidence: 89%
“…General hypothermia needs to have a sufficient depth and duration of cooling in order to attain significant neuroprotection (Dumitrascu et al, 2016;Maier et al, 1998;van der Worp et al, 2007;Yenari and Han, 2012). Maier et al (Maier et al, 1998) demonstrated that more than 4°C of cooling and more than 30 minutes of therapy are required to successfully attain significant neuroprotection in ischemic stroke models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…141 A meta-analysis of 60 animal models of ischemic stroke described various degrees and timings of hypothermia 34 and different stroke induction models and lesion volumes. This study identified robust benefits of hypothermia in preclinical animal studies.…”
Section: Hypothermia and Preservation Of Cerebral Function Following mentioning
confidence: 99%
“…These findings reinforce the central role of TRP channels as molecular thermometers, and may open new avenues for the clinically controlled modulation of T core . For instance, there is evidence that mild hypothermia can reduce neurological damage after stroke or cardiac arrest [10], therefore targeted activation of TRPM2-expressing WSNs in the POA may represent an alternative approach to current elaborate physical cooling procedures.…”
mentioning
confidence: 99%